Africa: Africa's Counter-Cyclical Policy Responses to the Crisis - Kasekende, Louis (De Gruyter, 2010)
Louis Kasekende is Chief Economist of the African Development Bank (ADB). As Chief Economist, he is the Bank’s spokesperson on socio-economic and development issues of importance for Africa. He supervises the Development Research Department, the Statistics Department and the African Development Institute. He holds a PhD in Econometrics and MA in Economics from University of Manchester, UK; as well as a BA Economics degree from Makerere University, Uganda. Prior to joining the ADB, Louis Kasekende was Deputy Governor, Bank of Uganda. He worked for 17 years in the Bank of Uganda in several capacities, including as Director of Research Department and Executive Director with responsibility for Research and Policy. From 2002 to 2004, he was Executive Director, representing 22 African countries, on the Executive Board of the World Bank, USA. He has also served as a lecturer in Economics in Makerere University, Uganda, where he also supervised MA dissertations in a wide range of areas. Zuzana Brixiova is principal research economist at the African Development Bank’s Development Research Department. Formerly senior economist at the IMF, she worked on developing and transition economies in Africa and Central Asia. During 2002-04 she was the IMF's resident representative in Belarus and Lithuania. Prior to joining the Bank, she worked as the head of the Estonia and the Czech Republic desk in the OECD's Economics Department, covering the impact of the global financial crisis on macroeconomic policies and structural issues. In 2007-08 she was a Fulbright scholar in Ethiopia where she also guided several M.A. theses in macroeconomics. She holds Ph.D. in Economics from the University of Minnesota. Léonce Ndikumana is Director of the Development Research Department at the African Development Bank. Formerly Associate Professor of economics at the University of Massachusetts, Amherst, and Chief of Macroeconomic Analysis at the United Nations Economic Commission for Africa (UNECA), Léonce Ndikumana has contributed to various areas of research and policy analysis with a focus on African countries. He is an active member of major research networks around the world including the African Finance and Economics Association (AFEA) of which he is a former President, the African Economic Research Consortium (AERC) where he serves as resource person, and others
: Africa's Counter-Cyclical Policy Responses to the Crisis
Keywords: Africa; Inflation targetting; Counter-cyclical policy; Crisis